A case report on chronic massive pre-patellar bursa - Kumar, N. Venkatesh; Sundar, V. Shyam; Ramu, Saravana; Noel, V. Chandan (International Surgery Journal, 2016)
Inflammation of the pre-patellar bursa results in bursitis that is trouble free in most of the instances. It is most commonly caused by trauma to the knee, either by a single instance or by repeated trauma over time. Often they are associated with minimal swelling, very rarely do they present with large cystic swelling. Here, we present a case report on a large pre-patellar bursa in an elderly gentleman. Operative excision of the bursa was done in view of a sudden increase in size and pain. The biopsy revealed features of chronic bursitis. He had no recurrence of swelling or wound complications at follow-up.